Proactive and Post-Epidemic Behavioral Responses in a Periodic Environment with Delay: A Case Study of Influenza in Nova Scotia, Canada - El Hail, Khalid; Khaladi, Mohamed; Ouhinou, Aziz (Communication in Biomathematical Sciences, 2024)
We present a delayed epidemic model in a periodic environment, taking into account behavioral changes. The model combines two types of behavioral responses: one responding to the progression of the epidemic and the other based on independent education of the epidemic. We establish the global stability of the diseasefree equilibrium and validate the model using real influenza data in Nova Scotia, Canada. Using numerical simulations, we compare the effects of behavioral changes early on with those that occur as the epidemic progresses. Our results highlight the important role of early and sustained educational efforts in controlling the spread of disease. Additionally, we examine the sensitivity of the basic reproduction number to various parameters, revealing that R0 is especially responsive to those associated with continuous education.